Bilateral deficit in handgrip strength is not associated with rowing ergometer performances - Pauleti, J. C.; da Silva, C. S.; Ventura, T. P.; Borszcz, F. K.; Possamai, L. T.; Turnes, T. (Research in Sports Medicine, 2025)
The bilateral deficit (BD) is the reduced force in bilateral versus unilateral contractions. This study investigated BD in handgrip strength of 13 trained rowers and its relation to rowing ergometer performance (500 m, 1000 m, 2000 m). No difference was found between bilateral (95.4 ± 13.3 kgf) and unilateral forces (95.2 ± 14.7 kgf; p = 0.902), indicating no BD (0.4 ± 4.3%). The bilateral index did not correlate with performance in 500 m (r = -0.097), 1000 m (r = -0.576), or 2000 m (r = -0.399). These findings suggest that trained rowers do not exhibit BD, and this measure is not associated with performance.